Exploratory Evaluation of Circulating Microbiota-Derived Corisin Levels in Women with Adverse Pregnancy Outcomes - Maya Kato; Masafumi Nii; Kuniaki Toriyabe; Yuya Tamaishi; Sho Takakura; Shoichi Magawa; Taro Yasuma; Corina N. D’Alessandro-Gabazza; Hajime Fujimoto; Masaaki Toda; Isaac Cann; Tetsu Kobayashi; et al. (Antioxidants, 2025)
Preterm birth and low birth weight remain major contributors to neonatal morbidity and mortality, yet the underlying mechanisms are not fully understood. Maternal microbiota has been implicated in adverse pregnancy outcomes, but key mediators remain unidentified. We previously showed that the microbiota-derived peptide corisin induces epithelial apoptosis via mitochondrial membrane depolarization and reactive oxygen species accumulation. In this retrospective preliminary study, we evaluated the association between maternal serum corisin levels and pregnancy outcomes in 84 eligible women. Among them, 10 experienced preterm birth, and 22 delivered low-birth-weight infants. Corisin levels were significantly elevated in these groups compared with women with full-term, normal-weight deliveries. Preterm birth was associated with increased tissue factor, while low birth weight correlated with higher thrombin–antithrombin complex and soluble thrombomodulin and lower fibrinogen levels. Corisin concentrations showed negative correlations with maternal BMI, birth weight and length, and estimated fetal weight. Positive correlations were observed between corisin, myeloperoxidase, and several coagulation markers. These preliminary findings suggest that elevated maternal corisin levels are associated with adverse pregnancy outcomes and may reflect underlying mechanisms involving oxidative stress and coagulation activation. Further investigation is warranted to clarify its potential role as a microbiota-derived biomarker in pregnancy complications.